2015
DOI: 10.1103/physrevb.91.144417
|View full text |Cite
|
Sign up to set email alerts
|

Spin diffusion in the low-dimensional molecular quantum Heisenberg antiferromagnetCu(pyz)(NO3)2detected with implanted muons

Abstract: We present the results of muon-spin relaxation measurements of spin excitations in the onedimensional quantum Heisenberg antiferromagnet Cu(pyz)(NO3)2. Using density-functional theory we propose muon sites and assess the degree of perturbation the muon probe causes on the system. We identify a site involving the muon forming a hydroxyl-type bond with an oxygen on the nitrate group that is sensitive to the characteristic spin dynamics of the system. Our measurements of the spin dynamics show that in the tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
2
17
1
Order By: Relevance
“…The λ B for ballistic spin transport in the 1D spin-1/2 Heisenberg antiferromagnet follows a logarithmic relation λ B  ∝ ln( J / B ). In contrast, for diffusive transport, the λ B obeys the B −0.5 power-law 16,17 . As shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The λ B for ballistic spin transport in the 1D spin-1/2 Heisenberg antiferromagnet follows a logarithmic relation λ B  ∝ ln( J / B ). In contrast, for diffusive transport, the λ B obeys the B −0.5 power-law 16,17 . As shown in the inset of Fig.…”
Section: Resultsmentioning
confidence: 96%
“…NMR studies on SrCuO 2 found diffusive relaxation (Thurber et al, 2001), while µSR experiments on high-purity samples in found ballistic relaxation (Maeter et al, 2013) (both studies probe k B T J). µSR measurements on an organic salt (Pratt et al, 2006) or on Cu(C 4 H 4 N 2 )(NO 3 ) 2 (Xiao et al, 2015) were interpreted in terms of diffusion, while a more recent µSR experiment (Huddart et al, 2020) 25 Recently, the spin-Seebeck effect was exploited to directly induce and measure spin currents in a quasi-1d cuprate material (Hirobe et al, 2017).…”
Section: A Quantum Magnetsmentioning
confidence: 99%
“…In addition to the materials measured in this study, also included is the half-substituted (Hpip) 2 Secondly, the longitudinal field (LF) geometry, intended to probe dynamics and applied to (Hpip) 2 CuCl 4 . Muon spin relaxation (μ + SR) has previously been shown to be a sensitive local probe of static and dynamic effects in one-and two-dimensional coordination polymer molecular magnets [13][14][15], in both TF and LF configurations. The technique has also been shown to usefully probe the phase diagram and excitations in systems based on coupled antiferromagnetic dimers [5] and in spin liquid systems [16], whose low energy physics can also be viewed as being related to that of antiferromagnetically coupled, strongly interacting dimers.…”
Section: Introductionmentioning
confidence: 99%